Adjuvant-free cellulose nanofiber vaccine induces permanent humoral immune response in mouse. (20th August 2022) - Ma, Ronglin; Xia, Wei; Zhang, Rui; Fan, Guojia; Sun, Libin; Qiu, Lei; Cui, Jinxin; Ju, Songwen; Wu, Pingping; Yang, Jie; Xiong, Jian; Yu, Qiang
Abstract: Vaccines have become one of the most effective strategies to deal with various infectious diseases and chronic noninfectious diseases, such as SARS virus, Novel Coronavirus, cancer, etc. However, recent studies have found that the neutralizing antibody titers induced by vaccines would drop to half level or even lower after vaccination. In this study, we designed a novel small-sized positively charged nanofiber-1 (PEI-CNF-1) as a vaccine carrier, which can induce a high long-term humoral immune response by controlled release of antigen. Further studies showed that PEI-CNF-1 could significantly induce the release of immune response factor IL-1 β and bone marrow-derived cell (BMDC) maturation. Moreover, compare to other cellulose nanofibers (CNFs), PEI-CNF-1 combined antigen (ovalbumin, OVA) induced and maintained the highest and longest antibody titers after vaccination. Interestingly, the antibody titers have no significant difference between at 21 and 90 d. Mechanically, we found that PEI-NCF-1 not only could control the slow-release of antigen, but also could be more easily swallowed by macrophages and metabolized by the bodies, thus presenting antigen more effectively. In conclusion, we believe that PEI-CNF-1 have a very high application prospect in inducing long-term humoral immune response, so as to achieve efficient prevention effect to epidemic viruses.